Artificial intelligence and legal responsibility - Annouar, Khennane; Mabrouk, Lachgueur (The International tax journal, 2025)
The article discusses the rapid development of artificial intelligence (AI) and the legal challenges it raises in determining responsibility for the actions of intelligent systems. It emphasises the difficulties of allocating responsibility among manufacturers, programmers and users, particularly when algorithms are capable of making semi-independent decisions. The article also emphasises the need to update current legal frameworks to keep pace with modern technological capabilities. It emphasises the importance of enacting clear legislation that protects individuals and society without hindering innovation. Ultimately, the article advocates a balanced legal approach to ensure accountability and transparency in the era of artificial intelligence.